ECONOMIC EMPOWERMENT FOR HUNTING AND GATHERING COMMUNITY IN MALAYSIA THROUGH ECOTOURISM ACTIVITIES IN THE NATIONAL PARK - Ibrahim, Asmawi; Abdullah, Ramle; Simin, Hafis Amat (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Kuala Koh National Park located in Kelantan is one of ecotourism destination is really beautiful with flora and fauna. This National Park is open to public since 1995. Ecotourism is a source to maintain the habitant and all live speciesdirectly including to maintain the culture of the aborigine as to increase their socioeconomic. This sector really has a good potential to develop an income for Batek Tribe which just hunting and gathering for their living. Some of BatekTribe which live nearby Kuala Koh National Park actively participate in some area of ecotourism directly. Therefore this paper will discuss about this three objectives: (i) to explain the economic activities among Batek Tribe at KualaKoh National Park. (ii) To determine the strength of Batek Tribe in increasing their socioeconomic through ecotourism. (iii) To explain the aspiration of Batek Tribe towards ecotourism activity. This research is conducted via qualitativemethod. Data is gathered by participation observation, interview and document analysis. The data is coordinated and analyze using QSR Nvivo application. Finding shows that Batek Tribe in Kuala Koh still hunting and gathering astheir main economic source. Many strength and skill have been recognized on Batek Tribe to increase their economy through their involvement in ecotourism in their area. Moreover, Batek Tribe have high aspiration to gain more workand income in ecotourism activity in Kuala Koh National Park.